Antifungal metabolites of biocontrol stain LB-1 and their inhibition mechanism against Botrytis cinerea - Zhang, Huan; Ji, Hongliang; Liu, Caiyun (Frontiers in Microbiology, 2024)
Introduction Chaetomium subaffine LB-1 is a novel biocontrol strain that produces non-volatile metabolites that inhibit the growth of Botrytis cinerea. However, the specific metabolites and antimicrobial mechanism of the strain LB-1 remains unclear. Methods In this study, the antifungal substances produced by strain LB-1, as well as the underlying mechanism of its inhibitory effect against B. cinerea, were explored using metabolomic and transcriptomic analysis. Results The results found that 45 metabolites might be the key antifungal substances, such as ouabain, ferulic acid, chlorogenic acid, spermidine, stachydrine, and stearic acid. The transcriptomic analysis indicated that the inhibition effect of LB-1 on B. cinerea resulted in the upregulation of genes related to adenosine triphosphate (ATP)-binding cassette (ABC) transporters, peroxisome, ER stress, and multiple metabolic pathways, and in downregulation of many genes associated with the synthesis of cell walls/membranes, carbohydrate metabolism, cell cycle, meiosis, and DNA replication. Discussion These results suggested that the inhibitory effect of strain LB-1 against B. cinerea might be due to the destroyed cell wall and membrane integrity exerted by antimicrobial substances, which affect cell metabolism and inhibit cell proliferation.